A new odissey for the clinical cardiologist: the difficult application of arterial hypertension guidelines in patients with chronic coronary syndrome. (25th November 2020) - Cosmi, D; Mariottoni, B; Cosmi, F
Abstract: Introduction: In hypertensive patients with chronic coronary syndrome (CCS), the 2018 European Society of Cardiology (ESC) arterial hypertension guidelines recommend target pressure ranges that can be difficult to apply, leading to possible medico-legal and other not insignificant problems. Methods: In 2019 we evaluated blood pressure values measured according to the ESC 2018 recommendations in 2, 456 patients. We focused on 505 asymptomatic patients with CCS, already undergoing antihypertensive drug treatment. Patients with secondary hypertension, heart failure, atrial fibrillation, malignancies or life expectancy <1 year were excluded. We analyzed the incidence of high systolic pressure coexisting with diastolic pressure lower than the indicated target and the incidence of blood pressure below the targets indicated in asymptomatic patients in the various age groups considered. Results: In 24% of patients aged ≥80 years we found an office systolic blood pressure ≥140 mmHg together with a diastolic <70 mmHg, confirmed at the 2- and 4-week control. These values were also recorded in 18% of patients aged 65–79 years and in 5% of those aged 18–65 years. In asymptomatic patients aged 18–65 years old we found a systolic blood pressure <120 mmHg (considered not safe in the guidelines) in 4% of cases; SBP was <130 mmHg in 14% of patients aged 65–79 years and in 7% of those aged ≥80 years (considered not safe in the guidelines in these age group) (See table 1). Conclusions: The daily application of the ESC 2018 guidelines is challenging, due to contradictory suggestions (is it necessary to reduce a high systolic pressure ≥140 mmHg in the presence of a diastolic below the level considered dangerous <70 mmHg?; in an asymptomatic patient should therapy be reduced or suspended if blood pressure levels are not within the range considered optimal and safe?). This problem does not occur in American and NICE guidelines. We think that this topic should be largely reconsidered; guidelines writers should ask themselves these questions in order not to make hypertension treatment difficult or arbitrary. Funding Acknowledgement: Type of funding source: None